2003
DOI: 10.1103/physrevb.67.205304
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron x-ray photoelectron spectroscopy study of hydrogen-terminated6HSiC{0001}surfaces

Abstract: We report on highly resolved core-level and valence-band photoemission spectroscopies of hydrogenated, unreconstructed 6H-SiC(0001) and (0001 ) using synchrotron radiation. In the C 1s core level spectra of 6H-SiC(0001 ) a chemically shifted surface component due to C-H bonds is observed at a binding energy (0.47Ϯ0.02) eV higher than that of the bulk line. The Si 2p core-level spectra of SiC (0001) suggest the presence of a surface component as well but a clear identification is hindered by a large Gaussian wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
50
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 59 publications
13
50
0
Order By: Relevance
“…There are arguments, that may be some 30% smaller than given by the TPP calculations. 46 Nevertheless, the obtained value corresponds very well to the fact that all the Ga is laterally distributed in the topmost layer of the sample. After Ga metal deposition both the Ga 2p 3/2 and Ga 3d peak intensities increase due to the additional Ga on the surface but they remain significantly smaller than 1.…”
Section: -5supporting
confidence: 59%
“…There are arguments, that may be some 30% smaller than given by the TPP calculations. 46 Nevertheless, the obtained value corresponds very well to the fact that all the Ga is laterally distributed in the topmost layer of the sample. After Ga metal deposition both the Ga 2p 3/2 and Ga 3d peak intensities increase due to the additional Ga on the surface but they remain significantly smaller than 1.…”
Section: -5supporting
confidence: 59%
“…We have fit the spectra with a spin orbit split Si 2p peak (S2) and a second peak at higher binding energy (HBE) we associate with a SiC shifted surface state similar to the one observed for the clean SiC (3×3) surface. 13 The HBE peak forms after the first anneal and remains after further deposit and anneal cycles. When 1.4 ML of Si is evaporated at room temperature onto the 2 ML graphene, the Si 2p peak is larger and shifted 1.4eV to lower Binding Energy (BE).…”
mentioning
confidence: 99%
“…The binding energies of the components are 284.8, 284.1, and 283.4 eV. Those components can be assigned to C±C sp 2 orbitals such as those in graphite, hydrogenated SiC [25] (Si 3 C±H environment), and SiC, [26,27] respectively. The formation of SiC and the incorporation of hydrogen in the compound is also supported by the study of the core-levelshifted components of the Si 2p photoemission peak (not shown).…”
mentioning
confidence: 99%